Synthetic biology category wins the 350th Anniversary Merck Innovation Cup - Matos, Ângelo Paggi; Kauffman, Amy; Vickery, Christopher; Naegeli, Kaleb; Strittmatter, Lisa; Sybirna, Anastasiya; van Blijswijk, Janneke; Adlung, Lorenz; Berbasova, Tetyana; Enterina, Jhon; Eismann, Lena; Tierney, Braden; et al. (Trends in biotechnology, 2020)
Over the past 350 years, Merck has developed science and technology especially in health care, life sciences, and performance materials. To celebrate so many productive years, Merck conducted a special expanded anniversary edition of the Innovation Cup in combination with the scientific conference Curious2018 - Future Insight in Darmstadt, Germany.